NARRATIVE INTERVIEWING: A CROSS-CULTURAL APPROACH FOR REHABILITATION PROFESSIONALS (Proceedings of the World Disability & Rehabilitation Conference, 2018)
Rehabilitation practitioners across a variety of clinical settings understand the importance of cultural sensitivity and rapport-building, in order to support client or patient engagement and follow-through with service plans for the attainment of clinical goals. The narrative interviewing technique is presented as a qualitative interview approach that is more in-depth than traditional interviews. It is a cross-culturally intrinsic method for exploring client concerns, promoting client reflection, deepening empathy for the client, and promoting deeper understanding of the client through storytelling – from intake through the process of termination. This platform is inherently person-centered and encourages opulent dialogue in a setting that is typically more prescribed.
Keywords: narrative; interviewing; rehabilitation; culture